Breast cancer care in Alberta: a Patients perspective - Crocker, Alysha; Anderes, Susan; Verbeek, Linda; Chobanuk, Janice; Olson, David W; Kortbeek, John; Elwi, Adam; Dean, Stafford; Estey, Angela; Quan, May Lynn (International Journal of Population Data Science, 2018)
Introduction Each year in Alberta, over 2,300 women are affected by breast cancer. In Alberta, a multi-year Breast Health Initiative is underway to improve breast cancer care; reduce wait times, coordinate care, and enhance patient experience. Patient reported experience measurements are important to inform and advance patient and family-centred care. Objectives and Approach The aim is to assess breast cancer patients’ experiences at two survey points; after surgeon consult and after breast surgery. Patients meeting inclusion criteria; highly suspicious of cancer on imaging result (i.e. BI-RADS 5), referral to Calgary or Edmonton breast program, English speaking, and having an email address are recruited by RN coordinators or nurse navigators. Automated survey invitations from REDCap are used. Seven days after the surgeon consult the first survey is sent and seven days after breast surgery the second survey is sent. Results Patient recruitment began November 27, 2017 and January 2, 2018 for Edmonton and Calgary, respectively. As of February, 2018, 45 patients had been recruited. Of these, the first survey was sent to 34 (i.e. seven days post surgeon consult) and 19 (56%) had completed the survey. All those eligible (18) agreed to participate in the upcoming second survey. Of those, six had provided their surgery date and the second survey which both were completed. Recruitment is ongoing until the conference, at that time there will be sufficient numbers to report findings. Conclusion/Implications Patient and family-centred care is an element of high-quality healthcare which AHS has identified as a priority. These results will report on the breast cancer patients’ perspectives and generate important information for clinicians and administrators to use for decision making and quality improvement of health services.